Delusionality of beliefs among 50 adult females with severe and extreme anorexia nervosa upon admission to an acute medical stabilization facility. - Kambanis, P. Evelyna; Bottera, Angeline R.; Mancuso, Christopher J.; Cass, Kamila; Lohse, Kristen; Benabe, Jodie; Oakes, Judy; Watters, Ashlie; Johnson, Craig; Mehler, Philip; Young, Kyle P. De (Eating Disorders)
We aimed to evaluate whether the content of eating/body image-related beliefs in individuals with anorexia nervosa (AN) was associated with important aspects of eating disorder (ED) psychopathology. Females with AN completed assessments within 96 hours of admission to an inpatient medical stabilization program. Study staff administered the Brown Assessment of Beliefs Scale and participants completed self-report measures. We derived belief content domains using an inductive approach and examined associations between beliefs and clinical variables. The following belief categories emerged (% with a belief in that category): body image beliefs (64%), food beliefs (30%), body function beliefs (20%), rejection of illness beliefs (12%), morality beliefs (10%), and control beliefs (6%). No one belief domain was significantly associated with greater delusional intensity. However, findings indicate that greater delusionality was generally associated with worse ED psychopathology.